Perceived Causes and Health Seeking Behaviours of Measles among Caregivers of Under-Five Children in Rural Communities in Anambra State, Nigeria - Dibia, Samuel Ifeanyi; Ezeani, Ugoma Deborah; Efiong, S. Samuel (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The study x-rayed the perceived causes and health seeking behaviour of caregivers of measles in under-five children in rural communities in Anambra State, Nigeria. A mixed design was adopted for the study. The study was carried out among the caregivers of children suffering of measles present in rural primary health care facilities in Anambra state. A sample of 240 caregivers was used for the study. Questionnaire and focus group discussion (FGD) guide served as instruments for data collection. Two hundred and forty caregivers were selected using multistage sampling technique. Twenty-five FGD participants were purposively selected. Descriptive statistics were used to summarize information on socio-demographic characteristics of respondents. The result of the study among others shows that only 82(34.2%) of the caregivers sought appropriate care. FGD reveals that misconceptions about childhood measles and traditional beliefs are prevalent in these areas. The study recommends the need to focus on interventions targeted towards addressing misconceptions about childhood measles since caregivers’ perceived cause and health seeking behaviour about childhood measles is not adequate, thus ensuring improvement in health seeking behaviour of caregivers. Training of patent medicine vendors may complement government effort in ensuring provision of appropriate health services in rural areas.